ESG as an Important Factor of Company Profitability and as a Moderation of Corporate Value - DINARJITO, Agung (International Journal of Environmental, Sustainability, and Social Science, 2024)
Environmental, social, and corporate governance (ESG) aspects are currently one of the important things that investors consider. This is related to the company's efforts to participate in protecting the environment to achieve sustainability. The ESG aspect is expected to be able to increase profitability which later with ESG can also affect company value. The purpose of this study is to analyze whether ESG can affect company profitability and firm value as well as moderate profitability to firm value. Samples were selected using a purposive sampling technique which was then analyzed using linear regression. The research object is a company listed on the Indonesia Stock Exchange from 2016 to 2021 that already has an ESG score, the data of which was obtained from Bloomberg. The results showed that ESG had no effect on profitability and firm value, profitability had a significant effect on firm value, and ESG had not been able to moderate profitability on firm value. The results of this study have implications that ESG aspects need to be aligned with company goals and improvements to all ESG aspects also need to be done. ESG is not only carried out to fulfill regulatory requirements.